Plan piloto para el desarrollo agro-industrial del cultivo de la yuca en algunos departamentos de la Costa Atlantica de Colombia : Segundo informe julio 1982-mayo 1983 - Gómez G., Guillermo G. (International Center for Tropical Agriculture, 1983)
Activities of the collaborative project Integrated Rural Development Program (DRI)/Canadian International Development Agency- CIAT for the agroindustrial development of cassava on the Colombian Atlantic Coast are reported for the period July 1982-May 1983. Efforts concentrated on the expansion of the drying areas of the Betulia pilot plant in Sucre from 300 to 1000 square meters and the construction of 6 additional plants (2 in Sucre, 1 in Cordoba, 1 in Atlantico, and 2 in Magdalena). Economic data are presented regarding updated investments and returns to operate cassava drying plants with drying areas of 500 and 1000 square meters. Partial results of a survey of cassava production and marketing in the region are given. Collaborative agronomic research was conducted at different sites to compare the productivity of cassava var. Venezolana, M Col 1684, and the hybrid CM 342-170 in monoculture and in association with maize and yams; M Col 1684 was superior in both cropping systems, but the productivity of the local var. Venezolana could probably be increased with improved technology. Training activities are reported as well as preliminary observations on the development of appropriate technology for artificial cassava drying and its combination with natural drying. (CIAT)